Adaptasi Masyarakat Menghadapi Perubahan Iklim dalam Ketersediaan Air Minum - Heston, Yudha Pracastino; Febrianty, Dessy (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2013)
The climate change also increases water crisis caused by the length of dry season, especially on regions with lesser amount of water. The impact on water area consequently affects social aspects. City as center of activities becomes a vulnerable place to the impacts of climate change. The research question is regarding strategy of community adaptation to the climate change impact on drinking water, focusing on finding community readiness strategy. The study is conducted with qualitative–quantitative approach. Data analysis uses thematic analysis method, by which inductive data is analyzed based on a bunch of data collected, and processed using the principles of inductive reasoning. Resulting theory is composed from hypothetical assumptions and checked with the data. Quantitative analysis is followed by a descriptive statistical analysis, inferential and adaptation valuation. The analysis shows that communities have adapted autonomously to the drinking water availability according to its context, content, attributes and adaptation process. Areas with water scarcity (such as Kupang and Gunung Kidul) have better institutional and community preparedness than areas with abundance of water. However, they require more adaptation efforts. Adaptation can be measured with quantitative data, such as infrastructure, commercial businesses, health settlement and general population, as well with qualitative data: the readiness of individuals, communities and institutions.